Heat exposure in sugarcane workers in Costa Rica during the non-harvest season - Jennifer Crowe; José Manuel Moya-Bonilla; Bryan Román-Solano; Andrés Robles-Ramírez (Taylor & Francis Group, 2010)
This observational pilot study was carried out at three sugarcane companies in Costa Rica. Its main objective was to determine the potential for heat stress conditions for workers in one sugarcane-growing region in Costa Rica during the maintenance (non-harvest) period.Wet bulb globe temperature (WBGT) variables were measured with a heat stress meter and threshold value limits and the Sweat Rate Indexes were calculated for each workplace. It was determined that workers in this study were in heat stress conditions. Costa Rica is likely to experience warmer temperatures and increased heat waves in the coming decades. It is therefore important to take action to decrease current and future heat-related risks for sugarcane workers in both harvest and non-harvest conditions and in all sugarcane growing regions in Costa Rica. It is also necessary to improve guidelines and occupational health standards for protecting worker health and productivity in the tropics.